1998
DOI: 10.1007/s002210050525
|View full text |Cite
|
Sign up to set email alerts
|

The precision of proprioceptive position sense

Abstract: The purpose of this study was to determine the precision of proprioceptive localization of the hand in humans. We derived spatial probability distributions which describe the precision of localization on the basis of three different sources of information: proprioceptive information about the left hand, proprioceptive information about the right hand, and visual information. In the experiment subjects were seated at a table and had to perform three different position-matching tasks. In each task, the position … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

42
225
3
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(277 citation statements)
references
References 28 publications
42
225
3
1
Order By: Relevance
“…Although many researchers have noted that position sense requires a stored model of the body's metric properties (4,6,8), we believe that our systematic investigation of this body model is unique. Many models of position sense have simply assumed that the true metric properties of the body are known (5,7). In contrast, we show that the body model is massively distorted, at least in the case of the hand.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Although many researchers have noted that position sense requires a stored model of the body's metric properties (4,6,8), we believe that our systematic investigation of this body model is unique. Many models of position sense have simply assumed that the true metric properties of the body are known (5,7). In contrast, we show that the body model is massively distorted, at least in the case of the hand.…”
Section: Discussionmentioning
confidence: 67%
“…Proprioceptive signals from afferents in muscles, joints, and skin provide information about joint flexion or extension (1,2), contributing to a representation of body posture, the postural schema (3). To perceive the absolute position of body parts in external space, however, this postural information must be combined with information about the size and shape of the body segments connecting the joints (4)(5)(6)(7)(8) (Fig. 1A).…”
mentioning
confidence: 99%
“…Several other studies have also shown diVerences in performance between the arms (reviewed in Goble and Brown 2008). Important for the present study is the Wnding of Van Beers et al (1998), who demonstrated that the non-visual (proprioceptive) information about the position of the hand is not only more precise for the right hand for right-handed subjects, but also for left-handed ones.…”
Section: Introductionmentioning
confidence: 56%
“…Research suggests that localization judgments related to our body parts are based on the combination of proprioceptive signals (e.g. joint angles) and stored representation of body size and shape (Beers, Sittig, & van der Gon, 1998;Soechting, 1982). This stored representation of the body metric properties, referred to as the body model, was measured in a localization task for the hand .…”
Section: Introductionmentioning
confidence: 99%